Effect of FAA and BBA Aggregate Gradations on the Marshall Performance of Asphalt Concrete Mixtures for Airport Runway Applications - Viorentika Vigrid Yuniar Diergan Putri; Ervina Ahyudanari; Alifah Widya Rochmah (Yayasan Inovasi Kemajuan Intelektual, 2026)
Runway pavements are subjected to heavy and repetitive aircraft loads, requiring asphalt mixtures with high stability and deformation resistance. Aggregate gradation plays a critical role in controlling the mechanical performance of Asphalt Concrete (AC) mixtures. This study investigates the effect of FAA dense-graded and BBA open-graded aggregate gradations on the Marshall characteristics of AC mixtures for airport runway applications. Laboratory Marshall testing with 75 blows of compaction was conducted to evaluate stability, flow, Marshall Quotient (MQ), voids in mix (VIM), voids in mineral aggregate (VMA), and voids filled with asphalt (VFA). The results show that the optimum asphalt content (OAC) of the FAA mixture is 5.0%, while the BBA mixture requires a higher OAC of 5.6%. Under optimal conditions, the BBA mixture achieved a higher stability value (2270 kg) than the FAA mixture (2120 kg), indicating superior load-bearing capacity. The BBA mixture also exhibited higher VMA (15.82%) and VFA (77.38%), reflecting a stronger aggregate interlocking structure combined with higher asphalt content. These findings demonstrate that aggregate gradation philosophy significantly influences the mechanical performance of runway asphalt mixtures. The BBA gradation shows greater potential for use as a runway wearing course where high stability and resistance to deformation are required.